DETERMINANTS OF MUSCULOSKELETAL DISORDERS IN COFFEE PICKER IN KABUPATEN LUMAJANG - kurnia ardiansyah akbar (Universitas Darussalam Gontor, 2020)
Musculoskeletal disorders become a attention in theOcuupational health sector. One of the sectors that is affected is the agricultural sector. The results of previous studies indicate that musculoskeletal disorders in farmers will reduce up to 60% of farmer productivity. Musculoskeletal disorders are health problems that often occur in coffee pickers but are rarely noticed. Based on preliminary research from 30 respondents who were interviewed 100% of respondents claimed to experience rheumatic pain, cramps, sprains and numbness. Parts of the body that experienced complaints expressed by respondents had a variety of neck, right shoulder, left calf and waist. This complaint is an indication that coffee pickers have experienced musculoskeletal disorders. This study aims to analyze the musculoskletal disorders. The study was conducted on coffee pickers in 2 villages namely Tawon Songo and Jabon Villages Pasrujambe Kabupaten Lumajang with a total sample of 35 respondents taken by simple random sampling. The research design used was cross-sectional study. Based on the research results it was found that musculoskletal disorders were experienced by 32 respondents. Of the variables studied, two significant variables were risk factors for musculoskletal disorders, namely age (sig = 0.009) and burden (sig = 0.000).